Synergistic effect of hybrid size ZrO2 and electroless nickel decoration on the mechanical and high temperature oxidation properties of NiCr–ZrO2 composites - Kangarshahi, Leila Momeni; Sajjadi, Seyed Abdolkarim; Pour-Ali, Sadegh; Kiani-Rashid, Ali-Reza (Journal of alloys and compounds, 2020)
Four oxide dispersion strengthened (ODS) NiCr alloys were prepared by spark plasma sintering (SPS). 15 wt% ZrO2 as reinforcement was used in different conditions: (i) undecorated micro-ZrO2, (ii) undecorated hybrid size ZrO2 (12 wt% micro-ZrO2 + 3 wt% nano-ZrO2), (iii) electroless nickel (EN) decorated micro-ZrO2, and (iv) EN decorated hybrid size ZrO2. Microstructure, densification, mechanical properties, and high temperature oxidation at 900 °C of samples were comparatively investigated. According to the experimental results, the simultaneous presence of ZrO2 nanoparticles and EN decoration on ZrO2 particles resulted in maximum densification (relative density ≈ 98.9%) among the prepared ODS NiCr alloys. In this condition, hardness, flexural strength, and high temperature oxidation resistance also considerably increased. Typically, the hardness and flexural strength were respectively increased by around 25% and 33% compared with the reference ODS NiCr alloy (i.e. containing 15 wt% of undecorated micro-ZrO2 particles). Moreover, its weight gain during 96 h oxidation was about one-fourth of the reference one. Synergistic effect of EN decoration and choosing hybrid size ZrO2 particles on the mechanical properties and oxidation behavior was mainly attributed to the development of a desirable alloy/ceramic interface, filling the holes and gaps existing in the microstructure, and formation of a more dense structure. •A desirable NiCr/ZrO2 interface due to the EN-decoration of ZrO2 particles was obtained.•A synergistic effect was achieved with the EN-decoration and nano-ZrO2 addition.•The NiCr/EN-decorated hybrid size ZrO2 composite possessed the highest flexural strength.•The simultaneous presence of EN-decoration and nano-ZrO2 increases the oxidation resistance by around four times.•A schematic model was developed to describe the probable mechanism.